Personalizing adult spinal deformity surgery through multimodal artificial intelligence - Tej D. Azad; Vikas N. Vattipally; Christopher P. Ames (Acta Orthopaedica et Traumatologica Turcica, 2024)
To achieve meaningful, patient-centered outcomes following adult spinal deformity (ASD) surgery, it is crucial to engage in precise preoperative planning, perform excellent intraoperative execution, and ensure careful postoperative management. The field of multimodal artificial intelligence (AI) is rapidly developing and should be integrated into the management of ASD patients. In this context, we outline the current concepts and explore future applications of AI across the ASD care continuum.